Investment in resources to create value: but value for whom? - Salinas Ortiz, José (2023)
Value creation has long been a topic of great interest in management in general, and in strategic decision making in particular. Although many management approaches have described and explained what value "creation" means, some of them have focused on improving operations and therefore in value "delivery": how to align resources and activities to convert raw materials on finished products. Other approaches have focus on the “creation” of value for a particular type of stakeholders. This paper emphasizes the question of value creation as potential value, which revolves around the company's strategy; and also emphasizes the need to have a systematic and holistic approach that considers the different stakeholders of the company. If management doesn't understand the meaning of value, it could create something that is irrelevant to stakeholders. It will be shown that, in a competitive environment, to create value for investors in the long term, management must first create value for other stakeholders: customers, suppliers, employees and society.